2007
DOI: 10.1016/j.exphem.2006.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional analysis delineates the differential inflammatory response interleukin-15 elicits from cultured human T cells

Abstract: These findings suggest that exogenous IL-15 may have a potential role in adoptive immunotherapy by both enhancing proliferation and modulating functionality during ex vivo T-cell expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…IL-15 increases proliferation and immunoglobulin secretion by B cells as well as up-regulates expression of co-stimulatory molecules such as CD40L (42). In a study examining an experimental Pneumocystis vaccine in which CD40L was co-expressed, it was reported that antibodies to Pneumocystis were induced independent of CD4 + status (43).…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 increases proliferation and immunoglobulin secretion by B cells as well as up-regulates expression of co-stimulatory molecules such as CD40L (42). In a study examining an experimental Pneumocystis vaccine in which CD40L was co-expressed, it was reported that antibodies to Pneumocystis were induced independent of CD4 + status (43).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NFIL3 is induced by several cytokines and hormones, including IL-3, IL-4, IL-6, insulin, and PTH (8,9,(13)(14)(15)(16)(17)(18)(19). This suggests that NFIL3 is the critical mediator to induce cytokine-dependent cellular activation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65] Similarly, OSM expression can be induced in a STAT5-dependent fashion by other cytokines, including erythropoietin (Epo), G-CSF (granulocyte colony-stimulating factor), IL-2 and IL-3. 66-68 Additional STAT5-activating cytokines have also been shown to induce OSM expression, including GM-CSF (granulocytemacrophage colony-stimulating factor) 46,52,56,60 and IL-15, 69 although these studies did not directly confirm a role for STAT5. Notably, in response to GM-CSF or the protein kinase-C activator PMA (phorbol 12-myristate 13-acetate), neutrophils secrete considerable quantities of preformed OSM protein within minutes and continue to release newly synthesized OSM with prolonged stimulation.…”
Section: Regulation Of Osm Productionmentioning
confidence: 99%